Aspectos das relações de gênero no trânsito família/escola no plano de mobilização social pela educação - Costa, Janaína Carneiro da (2013)
This paper presents results of research carried out under the Masters Program of Graduate Studies in Education of the Federal University of Paraíba, in line Cultural Studies Education. The research investigated the discursive constructions of the family-school relationship and the gender dimensions within the Plan for Social Mobilization for Education (PMSE) in the period 2008-2011, with a spatial area in João Pessoa-PB. The PMSE integrates the strategies of Brazilian educational policy, the debate revolves around the "school failure" evidenced nationally, especially with the annual publication of the Index Numbers of Basic Education Development (IDEB). Along the lines of epistemologies argue that the character set and located the subjects in knowledge production - like Feminist Studies, Cultural Studies and Post-Colonial Studies - Reflections woven throughout the work are also affected by the experience of the author, given the intersections and interactions it has with the research topic. For data processing, the conceptual and methodological tools of discourse analysis were used, seeking to understand the strategies of social production in an attempt to reconstruct the discursive constructions of gender that pervade the PMSE and point out how they overflow in spaces where effective. Documents, images and events - the various constituent moments of PMSE were analyzed. The reflections arising from work are organized in four stages. The first present a reconstruction of the epistemological and theoretical-methodological field that dialogued. The second analyze material essential for implementation of the Manual PMSE-Mobilizer and Primer "Monitor the School Life of your children", page didactic-pedagogic tool of PMSE. The third retraces the moments of discursive actions of PMSE, highlighting the interview with the organizer of the State Committee for Mobilization, based in Joao Pessoa and the First International Seminar on Social Mobilization for Education - Interaction Family-School-Community. The fourth moment presents data on national implementation report PMSE (2008-2011). The paper concludes with some reflections on how the discourse constructed under the policy can constitute a mechanism for strengthening the naturalization of rape of a series of rights that should be extended to women, among them, to have available time to care themselves, eg, health, vocational training and leisure, subtracted due to the naturalization of the sphere of social reproduction as a female attribute. The perspective of the analysis presented in the paper is that it can open up new fronts of interrogation and questioning of gender issues and education policy.